2008
DOI: 10.1590/s0102-09352008000500027
|View full text |Cite
|
Sign up to set email alerts
|

Alimentação de leitoas pré-púberes com dietas contendo zearalenona

Abstract: RESUMOO desempenho, o peso de alguns órgãos e a morfologia vulvar de leitoas pré-púberes, alimentadas por 28 dias com dietas contendo zearalenona, foram avaliados. O delineamento experimental utilizado foi inteiramente ao acaso, com dois tratamentos, dieta controle (DC) e dieta controle + 2mg kg -1 de zearalenona (DZ), e seis repetições cada. Não houve diferença (P>0,05) entre os tratamentos para consumo médio diário de ração (1,24 x 1,19kg), ganho médio diário de peso (0,68 x 0,71kg), conversão alimentar (1,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
3
5
2
Order By: Relevance
“…This result differs from that obtained by Andretta et al (2008), who used 2mg/kg and observed increase of the vulva (vulvar volume) already in the first week of exposure of prepubertal females to ZEA. The differences in dose and time of exposure between studies reinforce the importance of these variables in the manifestation of clinical signs, especially when edema and hyperemia of the vulva are seen.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This result differs from that obtained by Andretta et al (2008), who used 2mg/kg and observed increase of the vulva (vulvar volume) already in the first week of exposure of prepubertal females to ZEA. The differences in dose and time of exposure between studies reinforce the importance of these variables in the manifestation of clinical signs, especially when edema and hyperemia of the vulva are seen.…”
Section: Discussioncontrasting
confidence: 99%
“…Signs of hyperestrogenism occurred in this experiment with lower doses of ZEA compared to other studies, which respectively used doses of 2mg/kg (Andretta et al 2008) and higher than 3mg/kg (Etienne & Jemmali et al 1982), respectively. In dose-response investigation with incremental concentrations of ZEA, Doll et al (2003) observed increased weight of uterus at low concentrations (0.42mg/kg).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Zearalenone did not influence (P . 0.05) the weight gain or the feed conversion in pigs, as had been observed in previous studies (Andretta et al, 2008). Weight gain was 21% lower (P , 0.05) in pigs challenged by mycotoxins compared with the control group (Table 2).…”
Section: Resultssupporting
confidence: 80%